Popular monster [compact disc] - Jelly Roll (Rapper); Tech N9ne (Rapper); Terrible, Alex (Epitaph, 2024)
Falling in Reverse makes anthems that provoke and inspire. Unnervingly ahead of the pack and yet always decisively right on time, their mix of bombastic declarations and intimate confessions connect with diverse crowds worldwide. This is their first full-length album in over seven years; an eleven song masterpiece, featuring five tracks that are bonafide smash hits, (three certified gold and one certified 2x platinum). Not ones to rest on their laurels, the six new tracks are incredible, and feature unexpected collaborations with some of the music industry hottest hitters.